Clinical significance of comprehensive genomic profiling tests covered by public insurance in patients with advanced solid cancers in Hokkaido, Japan. (3rd February 2021) - Kikuchi, Junko; Ohhara, Yoshihito; Takada, Kohichi; Tanabe, Hiroki; Hatanaka, Kazuteru; Amano, Toraji; C Hatanaka, Kanako; Hatanaka, Yutaka; Mitamura, Takashi; Kato, Momoko; Shibata, Yuka; Yabe, Ichiro; et al.
Abstract: Background: Comprehensive cancer genomic profiling has been used recently for patients with advanced solid cancers. Two cancer genomic profiling tests for patients with no standard treatment are covered by Japanese public health insurance since June 2019. Methods: We prospectively analyzed data of 189 patients with solid cancers who underwent either of the two-cancer genomic profiling tests at Hokkaido University Hospital and its liaison hospitals and whose results were discussed in molecular tumor board at Hokkaido University Hospital between August 2019 and July 2020. Results: All 189 patients had appropriate results. Actionable gene alterations were identified in 93 patients (49%). Frequent mutations included PIK3CA (12%) mutation, BRCA1/2 alteration (7%), ERBB2 amplification (6%) and tumor mutation burden-High (4%). The median turnaround time from sample shipping to acquisition by the expert panel was 26 days. Although 115 patients (61%) were provided with information for genotype-matched therapies, only 21 (11%) received them. Notably, four of eight patients below the age of 20 years were provided information for genotype-matched therapies, and three received them. Their response rates and disease control rates were 29% and 67%, respectively. Most patients who did not undergo the genotype-matched therapies were provided information for only investigational drugs in phases I and II at distant clinical trial sites in central Japan. Twenty-six patients were informed of suspected germline findings, while 11 patients (42%) received genetic counseling. Conclusions: The publicly reimbursed cancer genomic profilings may lead to the modest but favorable therapeutic efficacy of genotype-matched therapy for solid cancer patients with no standard therapy. However, poor access to genotype-matched therapy needs to be resolved. Abstract : Mini-abstract: Publicly reimbursed cancer genomic profilings lead to modest but favorable efficacy of genotype-matched therapy for solid cancer patients with no standard therapy, although poor access to genotype-matched therapy needs to be resolved.